Body Dissatisfaction Enhances Awareness and Facilitates the Consolidation of Body-Related Words During Rapid Serial Visual Presentation - So, Man Yi; Wang, Xinyu; Gao, Xiao (Frontiers in Psychology, 2019)
Attentional biases have received considerable focus in research on cognitive biases and body dissatisfaction (BD). However, most work has focused on spatial allocation of attention. The current two experiments employed a rapid serial visual presentation (RSVP) task to investigate the temporal allocation of attention to body-related words among young females with high and low BD. Experiment 1 assessed the stimulus-driven attention of body-related stimuli. Participants identified a neutral second target (T2) as accurately as possible while ignoring the preceding neutral, fat-, or thin-related first target (T1). As expected, we observed spontaneous attentional blink effects elicited by fat- and thin-related T1s among participants with high BD, suggesting enhanced awareness of body-related stimuli even when this information does not have to be identified. Such effects did not emerge among participants without BD. Experimental 2 investigated the goal-directed attention of body-related stimuli, during which participants needed to identify both the T1 and neutral T2. Participants with BD showed reduced attentional blink effects after both fat- and thin-related T1, suggesting facilitated consolidation of body-related information in goal-directed attention among participants with BD. The findings may have important clinical implications for understanding how to decrease and even prevent body image dissatisfaction.